Aspek Hukum dalam Pengelolaan Bisnis Koperasi Perkasa Nalo Tantan: Analisis Kepatuhan dan Tantangan Legalitas - Pertiwi, Alfiatun Oktafia; Trisnanta, Fhaiqa Bintari; Ardita, Fitria Jenni; Andini, Lija Eka (Universitas Batanghari Jambi, 2026)
This study aims to comprehensively analyze the legal aspects of the Perkasa Nalo Tantan Cooperative's business management, focusing on evaluating institutional and operational compliance and identifying legal challenges that may hinder the cooperative's effectiveness and sustainability. Considering that the Perkasa Nalo Tantan Cooperative operates in the real sector (oil palm plantations), this study uses empirical normative legal research (socio-legal research) with primary data from interviews (with the KSP Director, the Supervisory Board, and members) and secondary data from document studies. The findings indicate legal loopholes and substantive challenges. The compliance aspect in the capital sector shows unclear legal treatment of mandatory and voluntary savings, which has the potential to become a source of legal problems. Although financial transparency is considered good and meets the principles of Good Cooperative Governance, internal checks and balances remain weak. The biggest legal challenge lies in the operational aspect, where 55% of the Management Board experienced significant difficulties in obtaining sectoral land permits. This difficulty implies a threat to the legal standing of productive assets. Overall, while formal compliance is good, the biggest legal challenges lie in the operational substantive aspects and adapting to sectoral laws, which are more complex than basic institutional laws. Therefore, the Perkasa Nalo Tantan Cooperative requires a more proactive legal risk management strategy.